FILM PENYALIN CAHAYA (PHOTOCOPIER) KARYA WREGAS BHANUTEJA - Wayarits, Ridhani Abda (JOURNAL OF SCIENTIFIC COMMUNICATION (JSC), 2024)
Emphatically, film has formed an ideology about the meaning of metaphors, especially about sexual violence. This makes it clear that films delivered through mass media have a very large role in producing and constructing the meaning of metaphors about sexual violence by using Roland Barthes' semiotic perspective as the concept. In other aspects, there are many moral messages from each scene and scene and contain many meanings and positive messages for the community.Secara tegas film telah membentuk sebuah ideologi tentang makna metafora terutama tentang kekerasan seksual. Hal ini memperjelas bahwa film yang disampaikan melalui media massa memiliki peran yang sangat besar dalam memproduksi dan mengkonstruksi makna metafora tentang kekerasan seksual dengan menggunakan perspektif semiotika Roland Barthes sebagai konsepnya. Pada aspek yang lain banyak ditemui isi pesan moral dari tiap adegan dan scene serta mengandung banyak makna dan pesan yang positif bagi masyarakat.